FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERNIKAHAN DINI PADA WANITA DI DESA SERBANANTI KECAMATAN SIPISPIS KABUPATEN SERDANG BEDAGAI - Sari, Dian Maya; Saragih, Gina Novita (JURNAL KESEHATAN ALMUSLIM, 2021)
A teenager who is 20 years old and married can be called an early marriage. It is known that 10 women in Serbananti Village have been married at an early age, 7 of them married because of socio-cultural factors, economic factors, and educational factors. This study aims to know the factors associated with early marriage in women at Serbananti Village, Sipispis District, Serdang Bedagai in 2017. The type of research is analytical research with cross sectional design, the population is all women who have been married from 2012-2017 as many as 93 person. The entire population is sampled. Data were analyzed univariat and bivariate (with chi-square test). The results showed that there was a correlation between education, income, and trust (p-value of each variable = 0.000, 0.016 and 0.004) and there was not a correlation between profession and ethnic group (p-value of each variable = 0.124 and 0.143) with early marriage in Serbananti Village, Sipispis District, Serdang Bedagai in 2017. It is expected that the early marriage that occurs in the community is not increasing. Local Government to work with local health authorities to review and provide counseling and direct action on the community to prevent early marriage, and to provide knowledge about the dangers of early marriage to parents and young women.